2020
DOI: 10.3390/jof6040276
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in Children with Malignancies: Report from the Infection Working Group of the Hellenic Society of Pediatric Hematology-Oncology

Abstract: Candidemia is an important cause of morbidity and mortality especially in immunocompromised and hospitalized patients. We retrospectively collected data of candidemia cases that occurred in the seven Hematology-Oncology Departments/Units of Greece and the Stem Cell Transplant Unit between 2015 and 2019. In total, 19 episodes of candidemia in 19 patients were recorded. The majority of the patients (78.9%) had at least one risk factor for candidemia. The most frequent risk factors associated with candidemia obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Due to an increase in life expectancy in the high-risk population, such as children with immunosuppressed conditions and cancer patients, candida infections are becoming a more common pathogen for bloodstream infections connected with healthcare. Similar to earlier research (Vasileiou et al, 2020), non-albicans Candida species—particularly C.parapsilosis —were the most prevalent isolated species in the current investigation. A prolonged usage of central venous catheters was found to be highly associated with C.parapsilosis (Trofa et al, 2008) According to Devrim et al 2018, 2020), C. parapsilosis was the second most prevalent microbe in the pediatric hematology-oncology unit at the same study center.…”
Section: Discussionsupporting
confidence: 89%
“…Due to an increase in life expectancy in the high-risk population, such as children with immunosuppressed conditions and cancer patients, candida infections are becoming a more common pathogen for bloodstream infections connected with healthcare. Similar to earlier research (Vasileiou et al, 2020), non-albicans Candida species—particularly C.parapsilosis —were the most prevalent isolated species in the current investigation. A prolonged usage of central venous catheters was found to be highly associated with C.parapsilosis (Trofa et al, 2008) According to Devrim et al 2018, 2020), C. parapsilosis was the second most prevalent microbe in the pediatric hematology-oncology unit at the same study center.…”
Section: Discussionsupporting
confidence: 89%
“…Recent epidemiological studies of IFD pathogens have shown a higher proportion of non-Candida albicans yeasts and emergence of non-Aspergillus molds. 3,10,17,19,[26][27][28][29] In this cohort of children with solid malignancies, Candida parapsilosis predominated, and Aspergillus species and non-Aspergillus molds were rare. Notably, amongst patients who developed IFD in our study, 35.0% were receiving fluconazole antifungal prophylaxis.…”
Section: Discussionmentioning
confidence: 76%
“…The immunocompromised patients have possibilities of severe infections caused by environmental fungi including Wickerhamiella species. The mortality of non- Candida albicans species in pediatric patients with malignancies was 26.3% between 2015 and 2019 ( Vasileiou et al., 2020 ). The previous studies reported that the 5 patients with W. pararugosa bloodstream infections were immunocompromised because of malignancy, sarcoma, surgery, and leukemia, and 2 of the 5 patients could not be cured ( Nasri et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%